Oxygen Concentration-Dependent Oxidative Stress Levels in Rats - Nagatomo, Fumiko (Hindawi Publishing Corporation, 2012)
Introduction. We determined derivatives of reactive oxygen metabolites (dROMs) as an index of oxidative stress level (oxidant capacity) and biochemical antioxidant potential (BAP) as an index of antioxidant capacity in rats exposed to different oxygen concentrations. Methods. Male Wistar rats were exposed to 14.4%, 20.9%, 35.5%, 39.8%, 62.5%, and 82.2% oxygen at 1 atmosphere absolute for 24 h. Serum levels of dROMs and BAP were examined by using a free radical and antioxidant potential determination device. The morphological characteristics of red blood cells were examined by phase contrast microscopy. Results. There were no differences in the levels of dROMs in rats exposed to 14.4%, 20.9%, and 35.5% oxygen. However, the levels of dROMs increased in the rats exposed to 39.8% and 62.5% oxygen. The levels of dROMs were the highest in the rats exposed to 82.2% oxygen. There were no differences in the levels of BAP with respect to the oxygen concentration. Morphological changes in the red blood cells induced by oxidative attack from reactive oxygen species were observed in the rats exposed to 39.8%, 62.5%, and 82.2% oxygen. Conclusion. Our results suggest that exposure to oxygen concentrations higher than 40% for 24 h induces excessive levels of oxidative stress in rats.